Impact of SARS-CoV-2 positivity on clinical outcome among STEMI patients undergoing mechanical reperfusion: Insights from the ISACS STEMI COVID 19 registry - De Luca, Giuseppe; Debel, Niels; Cercek, Miha; Jensen, Lisette Okkels; Vavlukis, Marija; Calmac, Lucian; Johnson, Tom; Ferrer, Gerard Rourai; Ganyukov, Vladimir; Wojakowski, Wojtek; Kinnaird, Tim; von Birgelen, Clemens; et al. (Elsevier BV, 2021)
Background and aims SARS-Cov-2 predisposes patients to thrombotic complications, due to excessive inflammation, endothelial dysfunction, platelet activation, and coagulation/fibrinolysis disturbances. The aim of the present study was to evaluate clinical characteristics and prognostic impact of SARS-CoV-2 positivity among STEMI patients undergoing primary percutaneous coronary intervention (PPCI). Methods We selected SARS-CoV-2 positive patients included in the ISACS-STEMI COVID-19, a retrospective multicenter European registry including 6609 STEMI patients treated with PPCI from March 1 until April 30, 2019 and 2020. As a reference group, we randomly sampled 5 SARS-Cov-2 negative patients per each SARS-CoV-2 positive patient, individually matched for age, sex, and hospital/geographic area. Study endpoints were in-hospital mortality, definite stent thrombosis, heart failure. Results Our population is represented by 62 positive SARS-CoV-2 positive patients who were compared with a matched population of 310 STEMI patients. No significant difference was observed in baseline characteristics or modality of access to the PCI center. In the SARS-CoV-2 positive patients, the culprit lesion was more often located in the RCA (p < 0.001). Despite similar pre and postprocedural TIMI flow, we observed a trend in higher use of GP IIb-IIIa inhibitors and significantly higher use of thrombectomy in the SARS-CoV-2 positive patients. SARS-CoV-2 positivity was associated with a remarkably higher in hospital mortality (29 % vs 5.5 %, p < 0.001), definite in-stent thrombosis (8.1 % vs 1.6 %, p = 0.004) and heart failure (22.6 % vs 10.6 %, p = 0.001) that was confirmed after adjustment for confounding factors. Conclusions Our study showed that among STEMI patients, SARS-CoV-2 positivity is associated with larger thrombus burden, a remarkably higher mortality but also higher rates of in-stent thrombosis and heart failure.
Keywords: myocardial infarction; SARS-CoV-2; STEMI patients